Laparoscopic treatment of pyogenic liver abscess complicating Crohn's disease: A case report - (:unkn) unknown (TURKISH SOC GASTROENTEROLOGY, 2007)
Pyogenic liver abscess in patients with Crohn's disease is not common but the mortality has been reported to be high if diagnosis or treatment is delayed. Herein, we report the case of a 42-year-old man in whom multi-locular liver abscess was encountered in the right lobe of the liver as a complication of Crohn's disease. On his admission to the emergency unit, he had right upper quadrant pain, fever of 39 degrees C and hepatomegaly. Ultrasonography and abdominal computerized tomography demonstrated multi-locular pyogenic liver abscess in the right lobe of the liver. Percutaneous drainage failed because of the density of the pus; laparoscopic exploration was subsequently performed and 1500 ml pus was successfully drained. The patient became clinically stable without fever and with a decreasing white blood cell count on the third postoperative day.
Keywords: laparoscopic drainage of liver abscess; Crohn's disease; MANAGEMENT